2014
DOI: 10.5792/ksrr.2014.26.3.125
|View full text |Cite
|
Sign up to set email alerts
|

Medial Meniscus Posterior Root Tear: A Comprehensive Review

Abstract: Damage to the medial meniscus root, for example by a complete radial tear, destroys the ability of the knee to withstand hoop strain, resulting in contact pressure increases and kinematic alterations. For these reasons, several techniques have been developed to repair the medial meniscus posterior root tear (MMPRT), many of which have shown complete healing of the repaired MMPRT. However, efforts to standardize or optimize the treatment for MMPRT are much needed. When planning a surgical intervention for an MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
89
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 52 publications
(124 reference statements)
0
89
2
5
Order By: Relevance
“…Although surgical repair is currently seen as the treatment method of choice for PMMRTs, 3,36,37 the extra effort associated with this procedure requires justification from convincing outcomes. Regarding functional outcome scores, this systematic review shows a consistent and significant improvement in all scores used.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Although surgical repair is currently seen as the treatment method of choice for PMMRTs, 3,36,37 the extra effort associated with this procedure requires justification from convincing outcomes. Regarding functional outcome scores, this systematic review shows a consistent and significant improvement in all scores used.…”
Section: Discussionmentioning
confidence: 98%
“…3,36 Moon et al 30 analyzed prognostic factors of ATPR for PMMRTs in 51 patients and found that varus alignment of more than 5 and Outerbridge grade 3 or 4 chondral lesions were independent risk factors for poor clinical outcomes. Although indications and contraindications were only infrequently reported in the studies included in our systematic review, there is a broad consensus that root repair is only indicated in patients with no or only mild pre-existing OA (Kellgren-Lawrence grade I or II), good tissue quality of the meniscus, and willingness to follow a partial weight-bearing protocol for more than 6 weeks.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The most common presenting symptoms in meniscal root tears are posterior knee pain and joint line tenderness, especially with deep squatting 46. Another common symptom is a popping sound that is heard while participating in light activities, like ascending stairs or squatting 47. Seil et al 48 described a test that has proven useful in diagnosing a medial meniscal root tear.…”
Section: Guidelinesmentioning
confidence: 99%